2015
DOI: 10.1039/c4tx00241e
|View full text |Cite
|
Sign up to set email alerts
|

Hematotoxicity of magnetite nanoparticles coated with polyethylene glycol: in vitro and in vivo studies

Abstract: Hematotoxicity of magnetite nanoparticles coated with dimercaptosuccinic acid (DMSA) and polyethylene glycol (PEG) has been evaluated by determining their safety in vitro and in vivo in a rat model up to 30 days after administration of a single dose. The in vitro analysis consists of global plasma coagulation (PT, aPTT, and fibrinogen) and platelet aggregation tests while the hematotoxicity studies in vivo include a complete blood count and the possible genotoxic effect analysis in the bone marrow hematopoieti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Many studies showed that physicochemical properties of NPs can also induce destruction of erythrocytes with release of hemoglobin, leading to anemia and other pathological conditions . One of the mechanisms that plays a crucial role in hemolysis is the oxidative damage to erythrocyte membrane, rich of polyunsaturated fatty acids .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies showed that physicochemical properties of NPs can also induce destruction of erythrocytes with release of hemoglobin, leading to anemia and other pathological conditions . One of the mechanisms that plays a crucial role in hemolysis is the oxidative damage to erythrocyte membrane, rich of polyunsaturated fatty acids .…”
Section: Discussionmentioning
confidence: 99%
“…This slight decrease, that did not influence blood coagulation, as showed by APTT and PT tests, could be due to processes of absorption and/or binding of fibrinogen on NC surface, as observed in other studies investigating the affinity of plasma proteins for different NP surfaces. 36,37 Many studies showed that physicochemical properties of NPs can also induce destruction of erythrocytes with release of hemoglobin, 38,39 leading to anemia and other pathological conditions. 40 One of the mechanisms that plays a crucial role in hemolysis is the oxidative damage to erythrocyte membrane, rich of polyunsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some researchers evaluated the haematotoxicity of magnetic nanoparticles coated with dimercaptosuccinic acid (DMSA) and polyethylene glycol (PEG) in vitro and in vivo in a rat model. 19 In vitro analyses revealed prolonged APTT (activated partial thromboplastin time) values for DMSA compared with PEGcoated nanoparticles. There was a signicant effect on the leukocyte counts in animals treated with DMSA-coated nanoparticles compared with the PEG-modied group.…”
Section: Introductionmentioning
confidence: 97%
“…Nevertheless, it was suggested that nanoparticle administration might lead to cell damage; however, while using PEG-coated nanoparticles, no signs of hemolysis, genotoxic effects, or modulation of erythropoiesis were detected in female Wistar rats. PEG-coated nanoparticles do not have an impact on leukocyte count; thus are preferred [ 21 ]. However, PEG was shown to have an immunogenic effect, which may lead to faster clearance and lower target tissue accumulation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%